Financial Wellness Gen Z: The Influence of Financial Literacy, Behavior, Stress, Religiosity, Locus of Control, and FOMO - Windi Tri Pani; Susnaningsih Muat (Master of Management, School of Business and Management, Petra Christian University, 2025)
This study aims to determine the effect of financial literacy, financial behavior, financial stress, religiosity, locus of control, and fear of missing out (FOMO) on the financial wellness of Generation Z in Riau Province. Generation Z is a productive age group facing a transition from education to work, marked by consumerist patterns, social media influence, and financial management challenges. This study uses a quantitative approach, employing an online survey, to reach Generation Z in 10 districts and 2 cities in Riau Province. The sample used in this study was 402 respondents selected through purposive sampling. The respondents were Generation Z individuals born in 1997-2007, domiciled in Riau Province, and data analysis was conducted using SPSS and SmartPLS software version 4. The research findings show that financial literacy, behavior, and locus of control have a significant positive effect on financial wellness. Financial stress and religiosity have a positive but insignificant impact on financial wellness. Meanwhile, fear of missing out (FOMO) negatively impacts the financial wellness of Gen Z in Riau Province.